Hubungan Antara Kepuasan akan Gaji, Kecerdasan Emosional dengan Komitmen Kerja - Khasanah, Uswatun; Aulia, Lailatuzzahro Al-Akhda (ILMU PSIKOLOGI, 2020)
Commitment is an attitude that reflects the extent to which an individual knows and is tied to his organization. The commitment of employees to their organization is an attitude that reflects the degree to which individuals are identified with and involved with the organization and do not wish to leave the organization. There are many factors that can affect employee work commitment, one of which is salary satisfaction and emotional intelligence. The hypothesis in this study is "there is a relationship between satisfaction with salary, emotional intelligence and teacher work commitment. This research uses quantitative research methods. The population in this study amounted to around 285 teachers. The sampling technique uses quota sampling. Retrieval of data in this study using a work commitment scale, salary satisfaction scale, and emotional intelligence scale. For data analysis techniques, researchers used a two predictor regression formula. From the calculation, it is obtained Freg of 37.1791 with db of 2 against 47, it is obtained Ftable 1% of 5.18, and the terminan coefficient (R2) is 61.271%. With the effective contribution of satisfaction to the salary of 36.186% and the effective contribution of emotional intelligence of 25, 084%. Thus the results show that there is a very significant relationship between satisfaction with salary, emotional intelligence and work commitment of private junior high school level teachers in Pandaan district.